Bifurcation and Chaos in a Price Game of Irrigation Water in a Coastal Irrigation District - Baogui Xin; Yuting Li (Discrete Dynamics in Nature and Society)
We propose a price game model of irrigation water in a coastal irrigation district. Then, we discuss the stability and codimension-two period-doubling (flip) bifurcation. Then, the MATLAB package Cl_MatContM is employed to illustrate its numerical bifurcations-based continuation methods. Lastly, the 0-1 test algorithm is used to compute the median value of correlation coefficient which can indicate whether the underlying dynamics is regular or chaotic.